Analysis the Critical Factors of M-government Service Acceptance: An Integrating Theoretical Model between TAM and ECM - Mohammad Nurul Huda (Policy & Governance Review, 2023)
The development of smartphones has an essential role in digital services, which have the advantage of access to health services that can be performed anywhere and anytime. Unfortunately, the diffusion process of smartphone technology in the provision of health services faces the problem of decreasing the actual use of mobile health applications. Previous studies on m-government health services have also focused on using TAM and UTAUT to predict individual user behavior. A gap in the literature has been identified in previous studies. This study investigates the critical factors for the individual acceptance of m-government health services, especially the Peduli Lindungi mobile health service. The two theoretical models, TAM and ECM, were integrated to enhance the body of knowledge in predicting individual behavior in the m-government healthcare context. A quantitative method was used to analyse a total of 200 data. PLS-SEM was used to analyze the outer and inner models. The findings of this study support all hypotheses. The study's findings show that Perceived Usefulness, Perceived Easy to Use, and Satisfaction significantly affect on Intention Use; Perceived Usefulness, Perceived Easy to Use, and Expectation Confirmatory significantly affect on Satisfaction, Perceived Easy to Use has a significant effect on Perceived Usefulness. Expectation confirmation significantly affected Perceived Usefulness and perceived ease of use. The proposed model is successfully validated. Future research could consider integrating these theoretical models to assess the critical factors influencing the acceptance and use of digital services in other contexts.